Pressure, Opportunity and Predisposition: A Multivariate Model of Corporate Illegality - Baucus, Melissa S. (Journal of Management, 1994)
Corporate illegality researchers often maintain that wrongdoing occurs when factors pressure a firm to behave illegally, leading managers to make a rational decision to commit wrongdoing. Yet, corporate illegality results also from conditions of opportunity and predisposition, and it may be an unintended outcome of corporate actions. A multivariate model of corporate illegality is proposed, in which situational factors-conditions of pressure, opportunity, or predisposition-lead to unintentional and intentional illegality. The model distinguishes between intentional and unintentional illegal activities, and it recognizes that intentional illegality results from a decision to engage in wrongdoing, so characteristics of the individual decision maker affect the likelihood of wrongdoing. Implications of this model for researchers and managers are discussed.